Microplastics and Brominated Flame Retardants in Freshwater Fishes From Italian Lakes: Implication for Human Health - Pittura, Lucia; Tavoloni, Tamara; Ventura, Lucia; Stramenga, Arianna; d'Errico, Giuseppe; Lo Vaglio, Giovanni; Regoli, Francesco; Piersanti, Arianna; Gorbi, Stefania (Frontiers in Water, 2022)
Microplastics (MPs) and Brominated Flame Retardants (BFRs) represent a synergic threat for aquatic environments and organisms’ health status, with an additional concern on food quality and food security for species of commercial interest. In this study the ingestion of MPs, levels of polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCDs) were assessed in organisms from two lakes of Central Italy, with the aims of exploring the bioavailability of these pollutants in freshwater environments, the possible translocation of MPs from digestive to edible tissues, and the relationship between MPs ingestion and bioaccumulation of BFRs. The fish Perca fluviatilis, Anguilla anguilla, Carassus auratus and the crayfish Procambarus clarkii, all species commercialized for human consumption, were caught in Trasimeno Lake; moreover, P. fluviatilis and Rutilus rutilus were also sampled in Piediluco, a lake strongly influenced by industrial and anthropogenic activities, where fishing for commercial purpose is forbidden. With the only exception of C. auratus which showed the highest frequency of MPs ingestion (75%), species from Piediluco Lake exhibited a more elevated percentage of organisms positive to MPs ingestion (45%) and higher levels of PBDEs and HBCDs (mean values of 343 and 792 pg/g respectively in P. fluviatilis; 445 and 677 pg/g respectively in R. rutilus) than Trasimeno species (25% frequency of MPs ingestion, mean values between 6 and 163 pg/g for PBDEs and 5-107 pg/g for HBCDs). Polyester fibers dominated among MP typologies, and a high occurrence of man-made natural fibers was recorded. The number of MPs extracted in the gastrointestinal tracts of fish and soft bodies of crayfishes positive to MPs ingestion ranged between 1 and 2, while no MPs were found in fish fillets. Given these results, the risk related to human consumption of Trasimeno organisms appear very low, while further investigations are required to better elucidate the possible role of MPs pollution in modulating chemicals bioaccumulation in edible tissues. This study contributed to assess both environmental quality and food safety, reinforcing the use of bioindicator species for monitoring plans, in accordance with European recommendations.